Some Dictionary Descriptions of Grammatical Structure - Branford, William (Lexikos, 1991)
This paper examines some points in the treatment of grammatical structure in four recent dictionaries of English as L1. These are viewed against the background concepts of "lexicogrammar" (Halliday 1978) and of the interdependence of lexicographical and syntactic descriptions of language. Its scope is necessarily exploratory. The first of its three main sections is theoretical; the second examines some contemporary dictionary treatments of sentence, clause, and phrase; the third presents selected specifica, focussing on treatments of determiners, intensifiers and patterns of complementation, and on the "goodness of fit" between dictionary labellings and "structural descriptions" and the actual language system. Some necessarily tentative conclusions are drawn.